2021
DOI: 10.1016/j.cub.2021.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Wingtip folds and ripples on saturniid moths create decoy echoes against bat biosonar

Abstract: Highlights d A new defensive strategy against bats is identified among silkmoths d Acoustic tomography shows that wingtips of some silkmoths act as acoustic decoys d The folds and ripples on wingtips act as acoustic retroreflectors of bat calls d Forewing decoys evolved multiple times always as alternative to hindwing decoys

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Moths have evolved and developed varying acoustic defense mechanisms to counteract echolocating bats that prey upon them. Recent research has shown that certain moth species benefit from active or passive defense strategies to deter bats ( 1 ) including decoy echoes from wingtip ripples ( 2 ), acoustic stealth camouflage ( 3 5 ), and the emission of acoustic signals. Antibat sounds produced by moths may serve as warning signals (i.e., acoustic aposematism) ( 6 , 7 ) or jam a bat’s echolocation systems ( 8 , 9 ).…”
mentioning
confidence: 99%
“…Moths have evolved and developed varying acoustic defense mechanisms to counteract echolocating bats that prey upon them. Recent research has shown that certain moth species benefit from active or passive defense strategies to deter bats ( 1 ) including decoy echoes from wingtip ripples ( 2 ), acoustic stealth camouflage ( 3 5 ), and the emission of acoustic signals. Antibat sounds produced by moths may serve as warning signals (i.e., acoustic aposematism) ( 6 , 7 ) or jam a bat’s echolocation systems ( 8 , 9 ).…”
mentioning
confidence: 99%
“…Previous laboratory and field behavioural studies have greatly advanced our understanding of the behavioural outcomes of bat–moth interactions but have generally ignored the dietary composition of wild, free‐foraging bats (e.g. Acharya & Fenton, 1992; Barber & Conner, 2007; Corcoran & Conner, 2012; Corcoran et al, 2009; Dowdy & Conner, 2016, 2019; Dunning, 1968; Dunning et al, 1992; Fenton & Fullard, 1979; Neil et al, 2021). These studies often focus on individual anti‐bat tactics in moths, without simultaneously considering multiple moth anti‐bat tactics.…”
Section: Discussionmentioning
confidence: 99%
“…Moths have evolved a suite of counter-adaptations, including ultrasound-sensitive tympanate organs (ears) (Kristensen, 2012;ter Hofstede & Ratcliffe, 2016), ultrasonic clicks (Barber & Kawahara, 2013;Corcoran et al, 2009;Fullard et al, 1979), acoustic camouflage (Neil et al, 2020) and decoy echoes (Neil et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We then turned the impulse responses taken from all these directions into a tomographic image of the sample by an inverse Radon transform. To remove background noise, we then manually selected the image area containing the target object and then applied a Radon transform to extract only the aspects of the echo impulse responses originating from the target (for details see [ 22 ]). All spectral analyses, including for normal sound incidence, were based on echo impulse responses processed this way.…”
Section: Methodsmentioning
confidence: 99%